INTERROGATIVE SENTENCE ERROR OF PRAJA IPDN WEST KALIMANTAN CAMPUS IN CONVERSATION - Magpika Handayani (STBA Pontianak, 2017)
This study aims to see the dominant error made by praja IPDN west Kalimantan campus in conversation. In fulfilling these obligations, students of-ten find difficulty in asking in English. The study of dominant error in interrog-ative sentences in of praja IPDN west Kalimantan campus is a way to identify the problems of students in making interrogative sentences so that English con-versation program can run well and praja can ask question to each other with correct questions sentence pattern. The method used in this study is descriptive quaitative and the writer describes dominant error made by praja during the conversation. The data in the form of sentences obtained through list of ques-tions from conversation and interviews to determine the form of errors in making questions. The data obtained is then analyzed to obtain the results of research on the difficulties faced by praja in understanding the interrogative sentences. The results of this study show the most dominant error is in the sentence Yes / No verbs, and followed by Wh-question noun